2014
DOI: 10.13067/jkiecs.2014.9.12.1421
|View full text |Cite
|
Sign up to set email alerts
|

EEG Brainwave Analysis for Research on Meditation Influence to the Concentration

Abstract: Many people complain their big or little stress due to the complicated city life in modern times, so they are exposed of the mental illness. Especially, not only students and office workers but also most people suffer from degradation of efficiency at work and keeping the high quality of life because of the insufficiency of concentration ability. To improve the concentration ability, the meditation is a substitution. The influence of meditation for the concentration ability is experimented with EEG brainwave. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Brainwaves are, electrical flows that pass between the cranial nerves. They are the most important measures of the activities of the brain, and change depending on physical and mental states 13 , 14 , 15 ) . They are recorded via electrodes attached to the scalp in a neurophysiological measurement method of the electrical activity of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Brainwaves are, electrical flows that pass between the cranial nerves. They are the most important measures of the activities of the brain, and change depending on physical and mental states 13 , 14 , 15 ) . They are recorded via electrodes attached to the scalp in a neurophysiological measurement method of the electrical activity of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, meditation can help relieve stress. 8 9 Some studies have found that meditation can induce plastic changes in the brain, thereby creating new neurons and circuits. 10 11 …”
Section: Introductionmentioning
confidence: 99%